Spectacle of deformity : freak shows and modern British culture - Durbach, Nadja, 1971- (University of California Press, 2010)
In 1847, during the great age of the freak show, the British periodical Punch bemoaned the public's "prevailing taste for deformity." This vividly detailed work argues that far from being purely exploitative, displays of anomalous bodies served a deeper social purpose as they generated popular and scientific debates over the meanings attached to bodily difference. Nadja Durbach examines freaks both well-known and obscure including the Elephant Man; "Lalloo, the Double-Bodied Hindoo Boy," a set of conjoined twins advertised as half male, half female; Krao, a seven-year-old hairy Laotian girl wh